A double-weighted bankruptcy method to allocate CO₂ emissions permits - Stefano Moretti; Raja Trabelsi (Games, 2021)
Global warming, as a result of greenhouse gases, is exceeding the planet's temperature stabilization capacities. Thus, greenhouse gas emissions must be reduced. We analyse a bankruptcy situation aimed at allocating emissions permits of CO2, the predominant greenhouse gas emitted by human activities. Inspired by the Constrained Equal Awards (CEA) solution for bankruptcy situations, we introduce a new allocation protocol based on the extension of the CEA solution over double-weighted bankruptcy situations, including two exogenous parameters aimed at providing a balance, in the request of emissions permits, between economic activities and the production of renewable energy. In these bi-criteria allocation problems, we focus on a computational approach to find an allocation protocol that does not prioritize any particular parameter. As an application of our method, we first consider CO2 permit allocation problems in European Union (EU) countries, using real data about the gross domestic product (GDP), the production rate of renewable energies, and countries' 'demands' of CO2 emissions from 2010 to 2014. Then, we compare our approach with the CEA solution and its single-weighted extension to show the impact of using two weights over the distribution of CO2 emissions permits; we analyse the correlation between allocations of CO2 emission permits and the distribution of power within the EU Council to study the acceptability of alternative allocations.
Keywords: 330; bankruptcy situations; CO2 emissions permits; double-weighted allocation protocol